Development of Quizwhizzer Gamification Media in Bank Financial Industry Learning on Students' Learning Outcomes - Ayu Dewi Suryani; Muhammad Rahmattullah; Baseran Nor; Edy Suryanto (Economic Education Analysis Journal, 2025)
This study aims to develop gamification-based learning media using QuizWhizzer on the topic of the Bank Financial Industry. The research uses a Research and Development (R&D) approach with the 4D development model, which includes Define, Design, Develop, and Disseminate stages. The research subjects were Grade X students of SMAN 3 Banjarmasin enrolled in Economics, specifically in the topic of the banking financial industry. The sampling technique used was purposive sampling, involving 36 students per class. Data collection techniques included expert validation questionnaires, student response questionnaires, and learning outcome tests (pre-test and post-test). Data analysis techniques included validity analysis by media and material experts, practicality analysis based on student responses, and effectiveness analysis using the N-Gain formula to measure learning improvement. The results showed that the developed media was considered valid by experts, practical according to student assessments, and effective in improving learning outcomes, with an average N-Gain score of 0.7468, which falls into the high category. These findings highlight the importance of integrating digital learning media to enhance students’ academic performance. It is recommended that teachers adopt interactive and gamified learning platforms like QuizWhizzer to improve student understanding, engagement, and knowledge retention, leading to better overall learning outcomes in economics education.